In vitro effect of Q-switched Nd:YAG laser exposure on morphology, hydroxyapatite composition and microhardness properties of human dentin - Retna Apsari; Siswanto Siswanto; Anita Yuliati; Noriah Bidin (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: A Q-switched Nd:YAG laser was employed as a source of ablation. The fundamental wavelength of the laser is 1064 nm, with pulse duration of 8 nanosecond operates with uniphase mode of TEM00. In the following experiments, dentin samples (without caries and plaque) are exposed to pulse laser with Q-switching effect at various energy dose. Purpose: The aim of this study was to investigate the effect of laser ablation on dentin samples using Q-switched Nd:YAG laser exposure. Methods: The laser was operated in repetitive mode with frequency of 10 Hz. The energy dose of the laser was ranging from 13.9 J/cm2, 21.2 J/cm2 and 41.7 J/cm2. The target material comprised of human dentin. The laser was exposed in one mode with Q-switched Nd:YAG laser. Energy delivered to the target through free beam technique. The exposed human dentin was examined by using x-ray diffraction (XRD) and fluoresence scanning electron microscopy for energy dispersive (FESEM-EDAX). Microhardness of human dentin were examined by using microhardness vickers test (MVT). Results: The result obtained showed that the composition of hydroxyapatite of the dentin after exposed by Q-switched Nd:YAG laser are 75.02% to 78.21%, with microhardness of 38.7 kgf/mm2 to 86.6 kgf/mm2. This indicated that exposed pulsed Nd:YAG laser on the human dentin attributed to the phototermal effect. The power density created by the Q-switched Nd:YAG laser enables the heat to produce optical breakdown (melting and hole) associated with plasma formation and shock wave propagation, from energy dose of 21.2 J/cm2. From XRD analysis showed that the exposure of Nd:YAG laser did not involve in changing the crystal structure of the dentin, but due to photoablation effect. Conclusion: In conclusion, the application of Q-switched Nd:YAG laser as contactless drills in dentistry should be regarded as an alternative to the classical mechanical technique to improve the quality of the dentin treatment.Latar belakang: Mode Q-Switch pada laser Nd:YAG dapat menghasilkan fenomena ablasi pada dentin. Laser Nd:YAG yang digunakan mempunyai panjang gelombang 1064 nm, durasi pulsa 8 ns beroperasi dengan mode TEM00. Sampel dentin yang digunakan tanpa karies dan plak, yang dipapari laser dengan mode Q-switch dalam berbagai variasi dosis energi. Tujuan: Tujuan penelitian ini adalah mengamati efek ablasi dentin secara in vitro akibat paparan laser Nd:YAG Q-switch dengan pengamatan morfologi permukaan, komposisi hidroksiapatit, dan uji kekerasan mikro. Metode: Laser Nd:YAG Q-switch dengan frekuensi 10 Hz dan variasi dosis energi 13,9 J/cm2, 21,2 J/cm2 dan 41,7 J/cm2 ditembakkan pada sampel dentin manusia dengan teknik penyinaran bebas tanpa dilewatkan serat optik. Dentin yang terbuka diamati menggunakan x-ray diffraction (XRD) dan fluoresence scanning electron microscopy for energy dispersive (FESEM-EDAX). Kekerasan mikro dari dentin juga diamati menggunakan microhardness vickers test (MVT). Hasil: Hasil penelitian menunjukkan bahwa komposisi hidroksiapatit dari dentin setelah paparan laser Nd:YAG Q-Switch menunjukkan peningkatan berkisar 75,02% sampai 78,21% dibandingkan normal, dengan kekerasan mikro berkisar 38,7 kgf/mm2 sampai 86,6 kgf/mm2. Perubahan pada struktur mikro tersebut disebakan karena adanya efek fototermal. Kerapatan daya yang bervariasi berdasarkan variasi dosis energi menyebabkan efek panas pada dentin yang menyebabkan adanya fenomena optical breakdown, yang ditandai dengan munculnya efek leleh dan lubang pada sampel karena produksi plasma dan adanya gelombang kejut, mulai dosis 21,2 J/cm2. Berdasarkan uji XRD, efek yang muncul pada dentin tidak menyebabkan terjadinya perubahan struktur kristal hidroksiapatit, tetapi menyebabkan perubahan komposisi hidroksiapatit yang disebut dengan fotoablasi. Kesimpulan: Dapat disimpulkan bahwa penggunaan mode Q-switched pada laser Nd:YAG sebagai alat dengan kontak minimal dapat dijadikan teknik alternatif untuk meningkatkan kualitas perawatan dental.